PENGARUH KINERJA DISTRIBUSI FISIK DAN KUALITAS PELAYANAN TERHADAP CITRA PERUSAHAAN SERTA IMPLIKASINYA PADA LOYALITAS PELANGGAN (Survey pada Pelanggan PT. ATRI DISTRIBUSINDO di Bandung) - Santosa, Handi Dipo (JURISMA : Jurnal Riset Bisnis & Manajemen, 2018)
This study aims to obtain empirical evidence about the influence of physical distribution performance and quality of service to the company's image as well as the implications for customer loyalty in the PT Arri Distribusindo Bandung. The results are expected contribute to the development of management science and management especially marketing and consumer behavior. For those of similar companies and practitioners, ir is hoped the results of this study can provide useful information about the importance of physical distribution performance and quality of services, especially on the image of the company, which in num can increase customer loyalty as an evaluation tool. The study was conducted at PT Atri Distribusinda Bandung. Methods of research using survey methods with quantitative research approaches. While the ype of research the form Descriptive Explanation Verificative Research and Research with a time horizon in the form of cross-sectional data that reflects the picture of a state at a given moment. To test the hypothesis of statistical methods of research used path amalysis (path analysis).The test results of research found a significant relationship between the performance of physical distribution service qualin, as well as from the results of the test reveal significant influence of the physical distribution performance and quality of service to the company's image either partially or simultaneously, was also found significant relationship between the performance of the distribution plysical and quality of services to the corporate image that has implications for customer loyalty .Â Keywords: Performance of physical distribution, service quality, corporate image and customer loyalty